2000
DOI: 10.1088/0964-1726/9/4/309
|View full text |Cite
|
Sign up to set email alerts
|

Damage detection in bonded repairs using piezoceramics

Abstract: A smart structure is one that senses its internal state and external environment, and based on the information gained responds in a manner that fulfils its functional requirements. The primary advantage of moving towards smart structures technology is the potential cost benefit of condition-based maintenance strategies and the prospective life extension that may be achieved through in situ health monitoring. The monitoring of operational health and performance, and diagnosis of any faults as they occur, is a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Ultrasonic waves such as guided Lamb waves, which can propagate large distances in plate-like structures such as composite laminates, provide broader diagnostic coverage than conventional strain sensors for active structural health monitoring of composite structures [1][2][3][4][5].Lamb waves can be generated in composite structures by using an array of piezoelectric transducers, which are either surface bonded or embedded, and exciting with an alternating voltage, which produces contraction and expansion through the piezoelectric effect [6][7][8][9][10].…”
Section: Guided Waves and Its Significancementioning
confidence: 99%
“…Ultrasonic waves such as guided Lamb waves, which can propagate large distances in plate-like structures such as composite laminates, provide broader diagnostic coverage than conventional strain sensors for active structural health monitoring of composite structures [1][2][3][4][5].Lamb waves can be generated in composite structures by using an array of piezoelectric transducers, which are either surface bonded or embedded, and exciting with an alternating voltage, which produces contraction and expansion through the piezoelectric effect [6][7][8][9][10].…”
Section: Guided Waves and Its Significancementioning
confidence: 99%
“…We also note that various researchers combined the wave propagation theory with the piezoelectric sensing/actuating mechanisms to study passive and active structural health monitoring (SHM) systems [36][37][38][39]. For instance, the electromechanical impedance technique for SHM utilizes travelling waves and the electrical impedance of a surface-bonded PZT transducer to obtain the change in the electromechanical impedance signature of the structure and detects the structural damage by monitoring this change [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Then, it was concluded that modal frequency measurements are more appropriate as parameters in NDT of large structures than modal damping measurements. Chiu et al [14] analyzed a smart system aimed to detect debonding damage between the repair attachment and the metallic parent structure. They concluded that piezoceramic materials can be used reliably, providing in-service feedback on the bonding conditions.…”
Section: Introductionmentioning
confidence: 99%